Land reform and landholdings in Brazil - Juliano Assunç\~ao (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
Land and wealth are closely related in rural Brazil, a country characterized by high levels of inequality in terms of income or landholdings. After presenting a historical retrospective of land concentration and land reform in Brazil, this study evaluates the impact of the land reform programme undertaken in the 1990s on land ownership and land distribution. It is shown that the programme increased landownership among poor rural families and those with less educated household heads, reducing the fraction of the other families with landholding. Also, the land reform programme increased land inequality among landowners.
Keywords: D31; Q15; 330; land reform; land distribution; wealth distribution; Bodenreform; Grundbesitz; Brasilien